Executive Committee Minutes 2017-09-07 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 8/24/17 approved. Chair Report. Provost Report. Resolution regarding EO 1100 approved for Senate agenda. Discussion: Graduation Initiative 2025 allocation plan. Faculty Eligible for Emeritus Status approved for the Senate's consent calendar. Discussion of ACT meeting. FSAC Report. SAC Report. CFA Report. Associated Students Report. Senate agenda approved.